Group Dynamics and Individual Roles: A Differentiated Approach to Social-Emotional Learning. Issue 2 (4th March 2017) - Dugas, Daryl
ABSTRACT: Differentiated instruction is a set of strategies to help teachers meet each child where he or she is in order to improve students' engagement, lead them to do their best work, and maximize their success. This article describes a differentiated classroom management approach based in group dynamics which focuses on the development of group norms and roles. By teaching students about task and social-emotional roles, and about positive and negative roles, this approach provides venues for talking about student misbehaviors in a constructive way, helps students understand roles as something they choose rather than something they are, and gives every student new ways to shine in class by helping them discover their own unique roles that can contribute positively to the whole classroom group.